Penanaman Sengon dalam Gerakan Penghijauan di Desa Sukoharjo, Kecamatan Tirtomoyo, Kabupaten Wonogiri - Hery Widijanto; Suwarto Suwarto (PRIMA: Journal of Community Empowering and Services, 2019)
Title: Planting Sengon by Afforestation in Sukoharjo Village, Tirtomoyo District, Wonogiri Regency. This service activities aimed at introduce the vegetative conservation methods for minimized erosion and conserve land resources by afforestation with sengon. This activity was in collaboration with two partners, namely: (1) "Ngudi Mulyo" and (2) "Ngudi Tani I" Farmers Groups located in Sukoharjo Village, Tirtomoyo, Wonogiri. The business fields developed by the two partners were dry land agriculture. The problem that the land was hilly and rolling and more degradated due to high erosion. In this program, farmers will be introduced with vegetative method to reduced erosion and preserved land resources by reforestation with sengon. Activities included: preparation (coordination), procurement of seeds, fertilizers, tools and socialization on vegetative soil conservation method to reduced erosion and preserve land resources by reforestation with sengon. After the socialization and giving of sengon seeds, monitoring was carried out related to planting and maintenance. The results of the program  showed the enthusiasm of the community in participating both in socialization and planting of sengon seeds for reforestation